2018
DOI: 10.1038/s41598-018-23004-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and oceanographic tools reveal high population connectivity and diversity in the endangered pen shell Pinna nobilis

Abstract: For marine meta-populations with source-sink dynamics knowledge about genetic connectivity is important to conserve biodiversity and design marine protected areas (MPAs). We evaluate connectivity of a Mediterranean sessile species, Pinna nobilis. To address a large geographical scale, partial sequences of cytochrome oxidase I (COI, 590 bp) were used to evaluate phylogeographical patterns in the Western Mediterranean, and in the whole basin using overlapping sequences from the literature (243 bp). Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 60 publications
7
44
1
Order By: Relevance
“…In 2011, the current pattern was very different, with a major loss of larvae offshore towards southern waters predicted, likely leading to high mortality of larvae of that year class and a substantial decrease in recruitment. According to Wesselmann et al (), no isolation of the Balearic P. nobilis populations with the mainland was recorded. In fact, the locality of Ibiza appeared to be a key population in order to ensure connectivity, receiving genes from the mainland (the Ebro Delta, Alicante and Murcia) and exporting them to Mallorca.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In 2011, the current pattern was very different, with a major loss of larvae offshore towards southern waters predicted, likely leading to high mortality of larvae of that year class and a substantial decrease in recruitment. According to Wesselmann et al (), no isolation of the Balearic P. nobilis populations with the mainland was recorded. In fact, the locality of Ibiza appeared to be a key population in order to ensure connectivity, receiving genes from the mainland (the Ebro Delta, Alicante and Murcia) and exporting them to Mallorca.…”
Section: Discussionmentioning
confidence: 95%
“…However, no locality from our target region, the Spanish Western Mediterranean Sea, was included in any of these studies. Wesselmann et al () focused on population genetics of P. nobilis working at two spatial scales: (a) wide scale along the Mediterranean Sea using mitochondrial DNA (COI gene), and (b) small scale, including part of the Western Mediterranean Sea (Mediterranean Spanish coast and Balearic Islands) using 10 microsatellites. Microsatellite results showed isolation by oceanographic distance between sampling localities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results are suggestively robust considering some of the tested samples are from as far away as France. Additionally, Wesselmann et al (2018) demonstrated using microsatellite markers that populations of P. nobilis from across the Mediterranean have low inter-population diversity, while genetically having high connectivity, which suggests this marker will be useful for areas outside the Ebro Delta and into the Eastern Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of genetic diversity may find this region useful since regions rich in repeat sequences, such as those found here, frequently expand or contract during the course of evolution (Read et al, 2004); this being the basis for microsatellite analysis. Previous phylogenetic studies related to this genus have used more standard genetic markers such as cytochrome oxidase (Sanna et al, 2013(Sanna et al, , 2014, microsatellite DNA (Gonzalez-Wanguemert et al, 2015;Wesselmann et al, 2018), or nuclear and mitochondrial ribosomal genes (Lemer et al, 2014). In the case of the latter study, cryptic species were identified within the family Pinnidae.…”
Section: Discussionmentioning
confidence: 99%